Sustainability at its Core: Embracing the Essence of Tri Hita Karana Philosophy to Empower Eco-Tourism-Focused MSMEs in Bali - Sitiari, Ni Wayan; Datrini, Luh Kade; Sarmawa, Wayan Gede; Setini, Made (Journal of Finance and Business Digital, 2024)
Business sustainability is crucial for Bali's Micro, Small, and Medium Enterprises (MSMEs), especially in ecotourism. This study examines how Bali’s Tri Hita Karana (THK) philosophy—balancing relationships between God, humans, and nature—shapes MSME practices. Managers in Bali's MSMEs also encounter sustainability challenges in managing their businesses. The findings show that MSMEs implement THK values through offerings (mebanten) at designated spaces (pelangkiran), fostering social connections (menyamabraya), and practicing environmental conservation. Despite THK's positive influence, challenges arise in balancing traditional values with modern entrepreneurship. The study highlights the need for policies that promote entrepreneurial orientation while preserving local wisdom. Further research is recommended to explore the deeper role of THK in sustaining MSMEs